The McGraw-Hill handbook of english grammar and usage - Lester, Mark.; Beason, Larry (New York : McGraw-Hill, 2013)
Contains a practical guide to common English grammar, reviewing parts of speech, sentence structure, verb forms, and basic phrases while presenting tips on understanding mistakes and why they happen. Includes a glossary.
Includes index.
Adult.
Adult
Keywords: English language -- Grammar -- Handbooks, manuals, etc; English language -- Grammar -- Handbooks, manuals, etc; English language -- Usage -- Handbooks, manuals, etc; English language -- Usage -- Handbooks, manuals, etc